О выживаемости ооцист кокцидий кроликов в условиях юга Украины - Тимченко, А.Д. (Вестник зоологии, 1972)
Survival of unsporulated and sporulated Coccidia oocysts in rabbits was studied in winter-spring period on the soil surface and at the depth of 5—10—20—30 cm under conditions of south Ukraine. It was established that unsporulated oocysts die on the surface and in the depth and only singular individuals (not more than 2.1 ±0.9%) preserve their viability. Sporulated oocysts preserve the viability especially at the depth of 5—10—20 cm and can evoke coccidious invasion.